Hydrogels of Poly(2-hydroxyethyl methacrylate) and Poly(N,N-dimethylacrylamide) Interpenetrating Polymer Networks as Dermal Delivery Systems for Dexamethasone - Marin Simeonov; Bistra Kostova; Rositsa Mihaylova; Elena Vassileva (Pharmaceutics)
Background/Objectives: This study is an attempt to reveal the potential of two types of interpenetrating polymer network (IPN) hydrogels based on poly(2-hydroxyethyl methacrylate) (PHEMA) and poly(N,N-dimethylacrylamide) (PDMAM). These IPNs were evaluated for their potential for dermal delivery of the hydrophobic drug dexamethasone (DEX). Methods: The two types of IPNs were analyzed for their rheological behavior, swelling characteristics, and drug-loading capacity with DEX. Drug release profiles were studied in Franz diffusion cells in PBS media. Finally, the cytotoxicity of the PHEMA/PDMAM-based IPNs was studied against T-cell lymphoma cells (HUT-78) and a normal murine fibroblast cell line (CCL-1). Results: The rheological properties of these hydrogels show suitable mechanical properties for dermal application, with G′ values of ~10 kPa. From the rheological data, the mesh size of these hydrogels was found to be influenced by the type of the IPN and its composition, varying between 6.5 and 50 nm. The loading capacity of both IPN types and DEX entrapment efficiency were highly influenced by the IPN’s composition. The loading capacity of the IPNs can reach ~3.5%, with a DEX entrapment efficiency of ~35%. The PHEMA/PDMAM IPNs demonstrate an extended release profile with up to ~95% DEX released in 24 h, while PDMAM/PHEMA IPNs release no more than ~25% DEX in 24 h. The drug release profiles follow either non-Fickian diffusion (n~0.6) or case-II transport (n~0.9–1), depending on the IPN’s composition. The PHEMA/PDMAM-based materials were found to be non-cytotoxic against HUT-78 and CCL-1 cells. Conclusions: The study reveals that the IPNs of PHEMA and PDMAM appear to be suitable platforms for dermal delivery of dexamethasone as they have appropriate mechanical properties, providing tools to control drug loading and release, and they are biocompatible with human skin cells.